Ciclo de vida, importancia agrícola y manejo integrado de la chisa rizófaga Phyllophaga menetriesi Blanchard (Coleoptera: Melolonthidae), en Cauca y Quindío, Colombia Life cycle, agricultural importance and integrated management of the rhizophagous whitegrub, Phyllophaga menetriesi Blanchard (Coleoptera: Melolonthidae), in Cauca and Quindío, Colombia - Luis Carlos Pardo-Locarno; James Montoya Lerma (Acta Agronómica)
La biología e importancia agrícola de P. menetriesi, especie rizófaga, fue investigado en laboratorio y en cultivos del Cauca y Quindío (Colombia). El ciclo de vida fue anual, la duración de los estados (semanas) fue: huevo 2-3, primer instar 3-4, segundo instar 6-8, tercer instar 20-25, prepupa 2-3, pupa 4-5, adulto macho 4-6 y adulto hembra 4-8. El tamaño corporal (mm) por instar fue: primer instar anchura cefálica 1.85-2.04, anchura corporal 1.05-2.02 y la longitud 14.3-19.2, segundo instar 3.3-3.95, 4.02-5.1 y 24-35 respectivamente y en el tercer instar 5.8-6.02, 6.1-7.6, 56-67 respectivamente. El periodo reproductivo, estudiado mediante captura semanal en trampas de luz en Caldono, Cauca (2° 81'N y 76° 55'O, 1.450 msnm, precipitación pluvial 2.191 mm/anuales), fue corto, sincronizado con las lluvias de octubre-noviembre. El impacto económico, estudiado con muestreos mensuales de cuadrantes (1 m-2/25cm de profundidad) en Quimbaya, Quindío (04° 38´ 02" N y 75° 47´ 47" O; 1.274 msnm; 2000 mm/anuales), mostró que cinco larvas m-2 ocasionaron pérdida total de plántulas de maíz y yuca menores de dos meses; la abundancia fluctuó desde cero hasta 8 larvas m-2, evidenciando distribución "parchosa" y mayores densidades en pastizal y yuca. En lotes con antecedentes de la plaga deben monitorearse los adultos con trampas de luz como aviso temprano, catear larvas después de las lluvias de octubre y aplicar control microbiológico preventivo; niveles de 4 o más larvas m-2 podrían conjugar remoción de suelo, uso localizado de control químico e incorporación de fitomasa para fomentar la población de chisas saprófagas, diversidad trófica y enemigos naturales. The life cycle of Phyllophaga menetriesi was studied under laboratory conditions using samples taken from different crop systems in the departments of Cauca and Quindio, Colombia . The life cycle is annual and the developmental stages of this species were as follows: egg, 2-3 weeks; first instar, 3-4 weeks; second instar, 6-8 weeks; third instar, 20-25 weeks; prepupa, 2-3 weeks; pupa, 4-5 weeks; and adult, 4-6 weeks for males and 4-8 weeks for females. Cephalic width as well as body width and length (mm) were measured in the three instars, with the following results: first instar: 1.85- 2.04, 1.05-2.02, and 14.3-19.2, respectively; second instar: 3.3-3.95, 4.02-5.1, and 24-35, respectively; and third instar: 5.8-6.02, 6.1-7.6, and 56-67, respectively. The reproductive period of these insects was short and coincided with the rainy season (October-November), based on the results of weekly catches of insects using light traps in Caldono, Cauca (2° 81' N, 76° 55' W, 1450 m.a.s.l., and an annual pluvial precipitation of 2191 mm). To assess the economic impact of the insect, monthly samples were taken in quadrats ( 1 m² and 25 cm deep) in Quimbaya, Quindío (04° 38´ 02" N, 75° 47´ 47"W, 1274 m.a.s.l., and an annual precipitation of 2000 mm). Results showed that 5 larvae/m² produced total loss of maize and cassava plants less than 2 months old. Incidence ranged from 0 to 8 larvae/m², showing an irregular distribution. The highest densities were detected in pastures and in cassava crops. Plots with a history of incidence should be closely monitored using light traps as an early warning system. The presence of larvae should be determined immediately after the October rains and a microbiological control treatment has to be applied as preventive measure. Levels of 4 larvas/m² or above could exact soil removal, localized use of chemicals, and incorporation of phytomass to promote saprophagous grubs, trophic diversity, and natural enemies.